Predisposing factors for breastfeeding in the first hour of life. - Francisco de Azevêdo, Joicy Amorim; Rolim de Holanda, Eliane; Wanderley Matos de Abreu, Danilo; Rolim de Holanda, Viviane (Rev Rene, 2023)
Objective: to investigate the prevalence and predisposing factors to breastfeeding in the first hour of life in public maternity hospitals. Methods: this is a cross-sectional, analytical, and exploratory study of 390 puerperal women from two public maternity hospitals. Sociodemographic characteristics, obstetric history, and variables relating to labor, delivery, and postpartum were analyzed. Statistical differences were assessed using the chi-square test or Fisher's exact test. The prevalence ratio was calculated using Poisson regression with robust variance. Results: the prevalence of breastfeeding in the first hour of life in the delivery room was only 29.2% (95% Confidence Interval: 24.68-33.71) and was associated with noise, the clamping of the umbilical cord, skin-to-skin contact, and the time taken to bathe the newborn for the first time. Conclusion: the predisposing factors for breastfeeding in the first hour of life were associated with care measures adopted during labor and birth, calling for strategies to improve care. Contribution to practice: the results can provide guidance for structural and educational changes, with a view to improving the care offered to the population during labor and birth.